Spectrophotometric Determination of Cinnarizine and Domperidone Maleate in Pharmaceutical Preparations by Ion Pair Complex Formation with Rose Bengal Dye - Abdussamed Saeed; Elham Salih (College of Education for Pure Sciences, 2019)
A simple, rapid and sensitive spectrophotometric method has been developed for the determination of cinnarizine (CIN) and domperidone maleate (DOM) in bulk and pharmaceutical formulations. The method is based on the formation of ion-pair complexes between the studied drugs and rose Bengal dye in buffer solution (pH5). The complexes give maximum absorbance at 571 nm. The method obeys Beer's law in the range of 0.5-34 and 0.5-36 µg ml-1 with molar absorptivity of 2.55×104 and 2.42×104 l.mol-1.cm-1 for CIN and DOM respectively. The method has been successfully applied for the determination of studied drugs on pharmaceutical dosages with no interferences. The results have been compared with official method and standard procedure with a good agreement.